Sustainable petrol subsidy program in Malaysia - Yen, Yuen Yee; Wen, Lai Jing; Ramasamy, Suganthi; Farooq, Muhammad (Asian Development Policy Review, 2023)
The purpose of this research is to propose a sustainable petrol subsidy program to enhance the effectiveness of the Malaysian government in subsidizing petrol to B40 and M40 households. B40 and M40 households, which suffered from poverty due to the COVID-19 pandemic. However, at the present moment, there is very limited study on the sustainable petrol subsidy program for B40 and M40 households. This research adopts a quantitative research method. One hundred and fifty questionnaires were disseminated to Malaysian B40 and M40 households. Sixty households responded to the questionnaire. This paper utilized cross-sectional design to test hypotheses that contribute to the sustainability of the petrol subsidy program in Malaysia post-COVID-19 pandemic. This paper has unique and important findings: household welfare, fiscal and macroeconomic issues, and environmental pollution are the most important factors that contribute to the sustainability of petrol subsidies in Malaysia. This research is the pioneering research in Malaysia that provides comprehensive insights on sustainable petrol subsidy, leading to a significant implication on the socio-economic wellbeing of the B40 and M40 households. It provides unique contributions to the government petrol subsidy in Malaysia, as it is one of the very limited studies in Malaysia post-COVID-19 pandemic.